Ionic liquids as solvents in biodiesel production. (14th September 2020) - Anitha, A.; Jini, D.
Biodiesel, an alternative fuel, has garnered much attention recently due to its eco-friendly nature. It is being produced using varied oil sources with the help of different catalysts and alcohols. Organic as well as inorganic solvents have widely been employed as catalysts, extraction agents and solvents in biodiesel production. But their toxic and hazardous nature has paved way for greener solvents like ionic liquids (ILs) owing to their environmental and process improvements. Low vapour pressure, good solubility and miscibility with co-reactants, better phase transition behaviour, high thermal stability, acidic and basic nature, and reusability make ILs very promising for use in biodiesel production. The main objective of this review is to highlight the versatility of ILs as solvents for biodiesel production.